New Liquidity Measurement: Mechanical Approach (Case of Pre Opening Session on IDX) - Kholisoh, Luluk (UI Scholars Hub, 2013)
The aim of this study is to develop a new liquidity measurement. The mechanical approach is used to measure the liquidity. This study uses trade order base that is more pronounced than conventional ones. To confirm the result of this study, we use pre opening session in the term of event as Kholisoh and Hermawati (2010) and Kholisoh (2011). This study collects trade base and order base intraday data one month period before and after pre opening session was implemented with the 25 most active stocks in LQ45. This study examines the velocity (how fast the order is executed) as new liquidity measurement. The result of this study confirms Kholisoh (2011), but contradicts to Kholisoh and Hermawati (2010) in the same event. The use of “velocity” as a metric of liquidity measurement is better in understanding the theoretical wisdom. This new liquidity measurement can cover the speed of the order to be executed in all capital market.